Inflammation-Mediated Angiogenesis in Ischemic Stroke - Zhu, Hua; Zhang, Yonggang; Zhong, Yi; Ye, Yingze; Hu, Xinyao; Gu, Lijuan; Xiong, Xiaoxing (Frontiers in Cellular Neuroscience, 2021)
Abstract: Stroke is the leading cause of disability and mortality in the world. But the pathogenesis of ischemic stroke (IS) is not completely clear and treatments are limited. Mounting evidence indicate that neovascularization is a critical defensive reaction to hypoxia that modulates the process of long-term neurologic recovery after IS. Angiogenesis is a complex process in which the original endothelial cells in blood vessels are differentiated, proliferated, migrated and finally remolded into new blood vessels. Many immune cells and cytokines as well as growth factors are directly or indirectly involved in the regulation of angiogenesis. Inflammatory cells can affect endothelial cell proliferation, migration and activation by secreting a variety of cytokines via various inflammation-relative signaling pathways, and thus participate in the process of angiogenesis. However, the mechanism of inflammation-mediated angiogenesis has not been fully elucidated. Hence, this review aims to discuss the mechanism of inflammation-mediated angiogenesis in IS and to provide new ideas for clinical treatment of IS.